Pengembangan Kurikulum Sekolah dalam Membentuk Peserta Didik yang Religius, Progresif, dan Berdaya Global - Yahya Rafi Sya’bani; Susanti Ariyanti; Aulia Pebriyanti Rahayu; Sofyan Iskandar (Jurnal Pendidikan Guru Madrasah Ibtidaiyah Al-Amin, 2025)
This study aims to analyze the development of a school curriculum at SD Labschool UPI Purwakarta in shaping students to be religious, progressive, and globally competitive. The main issues addressed are the challenges of curriculum development in elementary schools amid dynamic policies, teacher readiness, and changing educational demands. This qualitative study collected data through in-depth interviews and document analysis. The results show that SD Labschool UPI Purwakarta has developed three distinctive curricula: a religious-based curriculum through the Madrasah Diniyah Awaliyah (MDA) program, an ICT-based curriculum, and a bilingual curriculum. These are implemented through three learning track options (bilingual, tahfidz, and regular classes), offering flexibility for student potential development. These curricula strengthen students' religious values, digital literacy, and foreign language proficiency, and serve as the school's identity. This development reflects the school's strong commitment to preparing students who are spiritually grounded, digitally literate, and globally capable.